Gazing into the World of Tattoos: An Invitation to Reconsider how we Conceptualize Religious Practices. (June 2021) - Barras, Amélie; Saris, Anne
Debates around the visibility of religious symbols – including whether and how to regulate them—have been quite vivid in recent years in Canada, and particularly in the province of Quebec. These discussions often focus on minority religious symbols and are based on the premise that symbols can be removed or modified. In fact, Saba Mahmood (2006, 2009) argues that using the term "symbol" precludes de-facto our ability to entertain the possibility that these symbols cannot be removed or modified. Drawing on 15 interviews with religiously tattooed individuals and tattoo artists in Montreal and Toronto, this article explores the practice of religious tattooing. Interestingly, this practice has been overlooked in debates on the regulation of religious symbols, as well as in the scholarly literature covering those debates. In this article, we are interested in thinking about why this is. We also argue that looking at the practice of religious tattooing helps give further credence to Mahmood's criticism. It broadens our understanding of religious practices, including alerting us to the importance of the idea of 'lived religion' in comprehending how these practices can be an essential part of who someone is. While religious tattoos have largely escaped legal regulation, we conclude with a discussion of how they nonetheless remain the object of a regulatory gaze.